Revealing the relation between the structure, Li-ion conductivity and solid-state battery performance of the argyrodite Li6PS5Br solid electrolyte. Issue 40 (2nd October 2017) - Yu, Chuang; Ganapathy, Swapna; van Eck, Ernst R. H.; van Eijck, Lambert; Basak, Shibabrata; Liu, Yanyan; Zhang, Long; Zandbergen, Henny W.; Wagemaker, Marnix
Abstract : The relation between the argyrodite solid-electrolyte morphology and solid-state Li-ion battery performance is investigated, suggesting different morphologies for the electrode in combination electrolyte regions. Abstract : Based on its high Li-ion conductivity, argyrodite Li6 PS5 Br is a promising solid electrolyte for all-solid-state batteries. However, more understanding is required on the relation between the solid electrolyte conductivity and the solid-state battery performance with the argyrodite structure, crystallinity and particle size that depend on the synthesis conditions. In the present study, this relationship is investigated using neutron and X-ray diffraction to determine the detailed structure and impedance as well as 7 Li solid state NMR spectroscopy to study the Li-ion kinetics. It is found that depending on the synthesis conditions the distribution of the Br dopant over the crystallographic sites in Li6 PS5 Br is inhomogeneous, and that this may be responsible for a larger mobile Li-ion fraction in the interfacial regions in the annealed argyrodite materials. Comparing the bulk and interfacial properties of the differently prepared Li6 PS5 Br materials, it is proposed that optimal solid-state battery performance requires a different particle size for the solid electrolyte only region and the solid electrolyte in the cathode mixture. In the electrolyte region, the grain boundary resistance is minimized by annealing the argyrodite Li6 PS5 Br resulting in relatively large crystallites. In the cathode mixture however, additional particle size reduction of the Li6 PS5 Br is required to provide abundant Li6 PS5 Br–Li2 S interfaces that reduce the resistance of this rate limiting step in Li-ion transport. Thereby the results give insight into how to improve solid-state battery performance by controlling the solid electrolyte structure.